Developing Tomorrow’s Leaders: Applying Neuro-Linguistic Programming Techniques in Public Affairs Education and Human Resources Development - Van Rooyen, E. J. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Neuro-linguistic Programming (NLP) is a fast-growing educational, mentoring and coaching tool which embodies extensive applications in business school environments and public sector organisational contexts. Practitioners of NLP are excited by the prospect that this tool may assist to promote excellent performance and the expression of constructive leadership in various professional public affairs contexts; NLP techniques focus on reframing mind-sets positively, by taking cognisance of the sensory awareness functions of individuals, thus enhancing the flexibility to deal with evolving dynamics in the world we operate in. NLP can theoretically be infused in contemporary learning and teaching approaches to improve personal-professional development. It may enrich and innovate traditional methods, thereby increasing the extent of cognitive absorption (and comprehension) of complex managerial theorems and solving leadership quagmires. By emphasising the visual, auditory and kinaesthetic sensory functions, learning capabilities may be enhanced, and desired personal, inter-personal and organisational outcomes may be achieved to a greater extent. In other words, it may serve to reinforce efficient communication in organisations, hence establishing and maintaining high-level rapport between parties. In this paper, initial extrapolations are made from extensive desktop (secondary) research on NLP techniques in teaching and learning and mentoring and coaching, focusing on process over content. The above postulate is based on limited observations made by tracking a cohort of senior business students over a period of one year. The case example used is a Public Sector Accountancy module, which is traditionally viewed with apprehension because of the perceived 'difficulty' of such subject matter. Subsequently, an applied research phase is prefigured which should practically explore the impact of the introduction of NLP as a tool in teaching and learning at institutions of higher education and practical mentoring and coaching processes; therefore, engaging in an extensive longitudinal research voyage.
Journal article published in the International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Auditory; Emotional intelligence; Neuro-linguistic Programming; Sensory awareness; Neurolinguistic programming